The Gospel according to Isaiah 53 : encountering the suffering servant in Jewish and Christian theology - Bock, Darrell L.; Glaser, Mitch (Grand Rapids, MI, Kregel Academic, 2012)
The Gospel According to Isaiah 53 presents the redemptive work of the Messiah to the Jewish community, exploring issues of atonement and redemption in light of Isaiah chapter 53. --from publisher description.
Part 1: Interpretations of Isaiah 53 -- Christian Interpretations of Isaiah 53 / Richard E. Averbeck -- Jewish Interpretations of Isaiah 53 / Michael L. Brown -- Part 2: Isaiah 53 in Biblical Theology -- Identity and Mission of the 'Servant of the Lord' / Walter C. Kaiser, Jr. -- Isaiah 53 and the Message of Salvation in the Four Gospels / Michael J. Wilkins -- Isaiah 53 in Acts 8 / Darrell L. Bock -- Isaiah 53 in the Letters of Peter, Paul, Hebrews, and John / Craig A. Evans -- Substitutionary Atonement and Cultic Terminology in Isaiah 53 / David L. Allen -- Forgiveness and Salvation in Isaiah 53 / Robert B. Chisholm, Jr. -- Part 3: Isaiah 53 and Practical Theology -- Postmodern Themes from Isaiah 53 / John S. Feinberg -- Using Isaiah 53 in Jewish Evangelism / Mitch Glaser -- Preaching Isaiah 53 / Donald R. Sunukjian -- Conclusion / Darrell Bock -- Appendix A: Expositional Sermon on Isaiah 53 / Donald R. Sunukjian -- Appendix B. Dramatic-Narrative Sermon on Isaiah 53 / Donald R. Sunukjian.
Proceedings of a conference held in Mar. 2009 at Irving Baptist Church, Dallas, Tex.
Includes indexes.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Servanthood -- Biblical teaching -- Congresses; Bible. -- Criticism, interpretation, etc. -- Congresses; Servant of Jehovah -- Biblical teaching -- Congresses; Conference papers and proceedings; Criticism, interpretation, etc